Socioeconomic status, systolic blood pressure and intraocular pressure: the Tanjong Pagar Study. Issue 1 (23rd August 2006) - Yip, J L Y; Aung, T; Wong, T-Y; Machin, D; Khaw, P T; Khaw, K-T; Seah, S; Foster, P J
Abstract : Background: Lower socioeconomic status (SES) is associated with higher morbidity and mortality in many countries. Present evidence suggests that glaucoma has similar risk factors to major chronic diseases such as cardiovascular disease. This study investigates the association between SES and intraocular pressure (IOP), an important risk factor for glaucoma. Methods: The Tanjong Pagar Study was a population-based cross-sectional survey of Chinese people aged 40–79 years, who were randomly selected from the Singapore electoral register. Of the 2000 people selected, 1717 were considered eligible and 1090 were examined in clinic and included in the present study. IOP was measured using applanation tonometry. SES was assessed using a standardised questionnaire; education and income were used as the main explanatory variables. The effect of systolic blood pressure (SBP) was also examined. Results: Participants with lower levels of education and income had higher mean IOP (both p<0.01). These associations remained after adjusting for age and central corneal thickness, a strong independent predictor. SBP was strongly associated with both SES and IOP (both p<0.01). Adjusting for SBP attenuated the association between SES and IOP. Conclusion: Participants with lower education and income have a higher mean IOP. This effect may be mediated, in part, by an association of education and income with SBP. This is the first study to suggest that there is a social gradient in the distribution of the only major modifiable risk factor for glaucoma. Increasing similarities exist between the causation models of chronic diseases and that of glaucoma.